2018
DOI: 10.1063/1.5041771
|View full text |Cite
|
Sign up to set email alerts
|

Stability of plane Couette flow of Carreau fluids past a deformable solid at arbitrary Reynolds numbers

Abstract: The linear stability of the plane Couette flow of both power-law and Carreau fluids past a deformable, neo-Hookean solid is analyzed at arbitrary Reynolds numbers. An algebraic error in the mathematical formulation of the earlier studies (for the power-law fluid) is corrected and is shown to result in quantitative differences in the predictions for the stability of the flow. Due to the lack of a proper (zero-shear) viscosity scale and a time scale for the onset of shear thinning in the power-law model, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The viscous mode of instability predicted by Kumaran et al (1994), Kumaran & Muralikrishnan (2000) and Chokshi & Kumaran (2007) for the plane Couette flow past a deformable solid in the creeping-flow limit can be destabilised by increasing inertia. For Re > 10, the viscous mode of instability exhibits a characteristic scaling Γ c ∼ Re −1 (Chokshi & Kumaran 2008a;Tanmay et al 2018). However, from figure 10, the inertia has a stabilising effect on the solid elastic mode, which further sets apart the viscous mode of instability from the solid elastic mode predicted here.…”
Section: Non-zero Rementioning
confidence: 62%
See 1 more Smart Citation
“…The viscous mode of instability predicted by Kumaran et al (1994), Kumaran & Muralikrishnan (2000) and Chokshi & Kumaran (2007) for the plane Couette flow past a deformable solid in the creeping-flow limit can be destabilised by increasing inertia. For Re > 10, the viscous mode of instability exhibits a characteristic scaling Γ c ∼ Re −1 (Chokshi & Kumaran 2008a;Tanmay et al 2018). However, from figure 10, the inertia has a stabilising effect on the solid elastic mode, which further sets apart the viscous mode of instability from the solid elastic mode predicted here.…”
Section: Non-zero Rementioning
confidence: 62%
“…Their analysis predicted a non-monotonic effect of the variation in the power-law index on the viscous and short-wave modes of instability. Their work was extended to arbitrary Reynolds number by and Tanmay, Patne & Shankar (2018).…”
Section: Flows Past a Deformable-solid Layermentioning
confidence: 99%
“…As recently as 2019, inconsistencies have been found in previous calculations [196]. A theoretical re-analysis of a planar Couette flow over a compliant surface of a non-Newtonian fluid under the Carreau model showed that shear-thinning has a strongly stabilizing effect [197], with Re c ∼ Γ 3/(2n−1) , where Γ = Gh 0 /(V p η 0 ) and V p is the velocity of the rigid plate driving the Couette flow. Meanwhile, another experimental study [157] motivated the scaling Re c ∼ El −3/2 , where El = λ r η 0 /(a 2 ρ) is an elasticity number that characterizes the viscoelasticity of the polyacrylamide into water solution used.…”
Section: Microfluidic Mixingmentioning
confidence: 99%
“…As recently as 2019, inconsistencies have been found in previous calculations [193]. A theoretical re-analysis of a planar Couette flow over a compliant surface of a non-Newtonian fluid under the Carreau model showed that shear-thinning has a strongly stabilizing effect [194], with Re c ∼ Γ 3/(2n−1) , where Γ = Gh 0 /(V p η 0 ) and V p is the velocity of the rigid plate driving the Couette flow. Meanwhile, another experimental study [154] motivated the scaling Re c ∼ El −3/2 , where El = λ r η 0 /(a 2 ρ) is an elasticity number that characterizes the viscoelasticity of the polyacrylamide into water solution used.…”
Section: Microfluidic Mixingmentioning
confidence: 99%